FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHA TERNAK SAPI POTONG DI DESA REJODADI KECAMATAN SEMBAWA KABUPATEN BANYUASIN - Gultom, Nurlaili Fitri; Wahyuni, Reshi (Universitas Muhammadiyah Palembang, 2021)
The majority of cattle farmers businesses in Rejodadi Village Sembawa Disrict Banyuasin Regency are still managed in a small-scale traditional pattern with an average number of 3-5 cattle and are used as a side business, where the main business is plantation labor. The study aimed to : 1) Calculating the income from cattle business in Rejodadi Village, Sembawa District, Banyuasin Regency, 2) Analyzing what factors affect the income level of beef cattle business in Rejodadi Village, Sembawa District, Banyuasin Regency. This research was conducted in Rejodadi Village, Sembawa District. The location selection was done purposively, the research method used in this study was a survey method, for the sampling method was simple random sampling, which took as many as 30 respondents from 60 cattle breeders in Rejodadi Village. Based on the research results, the average income of beef cattle business in Rejodadi Village, Sembawa District, Banyuasin Regency is Rp. . 20,146,016. The factors that significantly affect the income variable of beef cattle business in Rejodadi Village are the cost of feeder cattle (X1), the cost of medicines (X2), the cost of feed (X3), the price (X4), the cost of the cage (X5). . While the variable that has no significant effect on livestock business income is the experience of raising livestock (X6).